2019
DOI: 10.1002/adfm.201902041
|View full text |Cite
|
Sign up to set email alerts
|

Atomic‐Scale Insights into the Low‐Temperature Oxidation of Methanol over a Single‐Atom Pt1‐Co3O4 Catalyst

Abstract: Changes made as a result of publishing processes such as copy-editing, formatting and page numbers may not be reflected in this version. For the definitive version of this publication, please refer to the published source. You are advised to consult the publisher's version if you wish to cite this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(62 citation statements)
references
References 49 publications
2
60
0
Order By: Relevance
“…In light of growing concerns associated with the emission of volatile or-ganic compounds (VOCs) [6][7][8][9], several recent publications have de-monstrated the potential of using SACs for the low-temperature de-struction of VOCs [10,11]. We too, recently demonstrated that a Pt1-Co3O4 SAC was exceptionally active for the destruction of oxygenated VOCs [12]. Despite the progress made, a great challenge remains; to develop thermally and chemically stable SACs, which required to be used in large scale traditional thermal reactions, such as catalytic combustion of hydrocarbons, water-gas shift and methane mineraliza-tion [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In light of growing concerns associated with the emission of volatile or-ganic compounds (VOCs) [6][7][8][9], several recent publications have de-monstrated the potential of using SACs for the low-temperature de-struction of VOCs [10,11]. We too, recently demonstrated that a Pt1-Co3O4 SAC was exceptionally active for the destruction of oxygenated VOCs [12]. Despite the progress made, a great challenge remains; to develop thermally and chemically stable SACs, which required to be used in large scale traditional thermal reactions, such as catalytic combustion of hydrocarbons, water-gas shift and methane mineraliza-tion [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the Fe oxides, the cation vacancies on other oxides have also been exploited for anchoring the single metal atoms, including the reducible oxides (e.g., CeO 2 , TiO 2 ) and the nonreducible oxides (e.g., Al 2 O 3 , NiO, ZnO, and MgO). [92][93][94] Combining theory and experiment, Neyman and co-workers demonstrated that the most stable sites for the surface Pt 2+ ions are the square O 4 nanopockets on the {100} facets, on which each Pt atom is coordinated by four O atoms. [86] More importantly, the isolated Pt 2+ species in the square-planar structure are thermally stable without reduction, sintering and bulk diffusion at elevated temperature.…”
Section: Surface Defects Engineeringmentioning
confidence: 99%
“…Jiang et al [123] prepared a 0.02 wt. % Pt 1 /Co 3 O 4 SAC that consisted of isolated single Pt atoms anchored to Co 3 O 4 (111) planes by occupying positions on the Co 2 + .…”
Section: Sacs For Oxidation Of Oxygenated Hcsmentioning
confidence: 99%